2018
DOI: 10.1182/blood-2017-10-812941
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 regulates CD4+ T cell–induced acute graft-versus-host disease in mice

Abstract: Abstract Nuclear factor erythroid-derived 2-like 2 (Nrf2) is a ubiquitously expressed transcription factor that is well known for its role in regulating the cellular redox pathway. Although there is mounting evidence suggesting a critical role for Nrf2 in hematopoietic stem cells and innate leukocytes, little is known about its involvement in T-cell biology. In this study, we identified a novel role for Nrf2 in regulating alloreactive T-cell function during allog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…showed that Nrf2 inhibits effector T cell activities independently of Tregs and that Nrf2‐mediated inflammatory effects in the context of autoimmunity required the integrity of Nrf2 mediated functional modulations of multiple cell lineages . More recently, it was reported that absence of Nrf2 in donor T cells enhanced persistence of Tregs and reduced systemic inflammation in a graft‐versus‐host disease in mice . Our study is the first to analyze Nrf2 activation specifically in Tregs by using Foxp3 cre Keap fl/fl mice and Foxp3 cre Keap fl/fl cell reconstituted BM chimeras.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that Nrf2 inhibits effector T cell activities independently of Tregs and that Nrf2‐mediated inflammatory effects in the context of autoimmunity required the integrity of Nrf2 mediated functional modulations of multiple cell lineages . More recently, it was reported that absence of Nrf2 in donor T cells enhanced persistence of Tregs and reduced systemic inflammation in a graft‐versus‐host disease in mice . Our study is the first to analyze Nrf2 activation specifically in Tregs by using Foxp3 cre Keap fl/fl mice and Foxp3 cre Keap fl/fl cell reconstituted BM chimeras.…”
Section: Discussionmentioning
confidence: 99%
“…TCR stimulation induces nuclear Nrf2 translocation and protein expression [10]. To further address the relevance of Nrf2 activity for T cell differentiation, we analyzed Nrf2 activation in isolated T cells during subsequent differentiation into distinct T cell subsets.…”
Section: Nrf2 Expression Driven By Foxp3 Specific Deletion Of Keap1 Imentioning
confidence: 99%
“…Activation of Nrf2 has been shown to negatively affect the maturation and effector functions in the related natural killer (NK) cells (Boss et al, 2018). Keap1 has been linked to T cell functions and thereby to inflammation (Ahmed et al, 2017; Noel et al, 2018; Tsai et al, 2018). T cell-specific deletion of Keap1 did not affect the conventional T cell numbers or percentages in the thymus, indicating that Keap1-Nrf2 is dispensable for T cell development (Noel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In our studies, contrary to the expectations, in ammation was not exacerbated in dystrophic muscles lacking transcriptionally active Nrf2 both when total in ammatory extent was evaluated on histological sections and by detailed analysis of immune subtypes by ow cytometry. Of note, despite the fact T h and T c lymphocytes contribute to the pathogenesis of DMD (6) and their functions may be regulated by Nrf2 (44), their numbers were changed neither by dystrophin nor Nrf2 de ciency. An interesting nding of our study is related to the NK cells' abundance -their number was signi cantly decreased in Nrf2 tKO mdx mice in comparison to mdx, in which they are elevated in the muscles (45).…”
Section: Discussionmentioning
confidence: 90%